Whole Genome Sequencing And Characterization Of Three Novel Mangrovimonas-Like Strains Isolated From Mangrove Forests Sediment In Perak, Malaysia - Balachandra, Dinesh (2017)
Strain TPBH4 (= LMG 28913, = JCM 30882), ST2L12 (= LMG 28914, = JCM 30880) dan ST2L15 (= LMG 28915, = JCM 30881) telah dipencilkan daripada sedimen muara di Perak, Malaysia